2022
DOI: 10.5493/wjem.v12.i4.53
|View full text |Cite
|
Sign up to set email alerts
|

Complement-mediated microvascular injury and thrombosis in the pathogenesis of severe COVID-19: A review

Abstract: Coronavirus disease 2019 (COVID-19) causes acute microvascular thrombosis in both venous and arterial structures which is highly associated with increased mortality. The mechanisms leading to thromboembolism are still under investigation. Current evidence suggests that excessive complement activation with severe amplification of the inflammatory response (cytokine storm) hastens disease progression and initiates complement-dependent cytotoxic tissue damage with resultant prothrombotic complications. The concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 116 publications
0
12
0
Order By: Relevance
“…First, SARS-CoV2 interacts with the angiotensin converting enzyme (ACE)-2 receptor on endothelial cells, which results in an increased release of the vasoconstrictor angiotensin-II and an endothelial dysfunction [ 158 ]. In addition, inflammatory response plays a primary role through complement activation, elevating levels of proinflammatory cytokines, such as interleukin-6 (IL-6) and IL-17A, which activate platelets, tissue factor and then the coagulation cascade [ 159 , 160 ]. Moreover, recent studies have shown alterations of both coagulation and fibrinolysis by multiple pathways, such as reduction of antithrombin and protein C and increasing of PAI-1 [ 160 , 161 ].…”
Section: Risk Factors For Venous Thromboembolismmentioning
confidence: 99%
“…First, SARS-CoV2 interacts with the angiotensin converting enzyme (ACE)-2 receptor on endothelial cells, which results in an increased release of the vasoconstrictor angiotensin-II and an endothelial dysfunction [ 158 ]. In addition, inflammatory response plays a primary role through complement activation, elevating levels of proinflammatory cytokines, such as interleukin-6 (IL-6) and IL-17A, which activate platelets, tissue factor and then the coagulation cascade [ 159 , 160 ]. Moreover, recent studies have shown alterations of both coagulation and fibrinolysis by multiple pathways, such as reduction of antithrombin and protein C and increasing of PAI-1 [ 160 , 161 ].…”
Section: Risk Factors For Venous Thromboembolismmentioning
confidence: 99%
“…Endothelial activation and innate immune system recruitment promote and stimulate the initiation of a procoagulant state, so-called immunothrombosis. 6,55,56 While the concept of a specific interaction between inflammatory processes with pro-coagulative mechanisms has been previously described, including general ARDS and sepsis which is not unique to COVID-19associated vasculopathies, immunothrombosis is considered as a pathologic key mechanism in the formation of microthrombi in COVID-19. 7,[57][58][59][60] Besides immunothrombosis, which defines a specific response of the innate immune system together with the coagulation system to destroy pathogens and restrict their dissemination, another term, called thromboinflammation, is also frequently used to describe the sole concomitance of inflammation and thrombosis.…”
Section: Immunothrombosismentioning
confidence: 99%
“…The complement system is a key mediator of the innate immune response and inflammation [ 84 ]. Lectin and alternative pathways mediate complement activation by SARS-CoV-2 S and N proteins [ 85 , 86 , 87 ], which will lead to EC and MC degranulation, enhanced phagocytic activity of neutrophils and monocytes, and “orchestration” of a proinflammatory environment [ 84 ].…”
Section: Biological Mechanisms For In Situ Pulmonary Immunothrombosismentioning
confidence: 99%
“…The complement system is a key mediator of the innate immune response and inflammation [ 84 ]. Lectin and alternative pathways mediate complement activation by SARS-CoV-2 S and N proteins [ 85 , 86 , 87 ], which will lead to EC and MC degranulation, enhanced phagocytic activity of neutrophils and monocytes, and “orchestration” of a proinflammatory environment [ 84 ]. Cleavage components C3a and C5a are potent inflammatory molecules capable of inducing the release of proinflammatory cytokines as part of the COVID-19-associated “cytokine storm” [ 87 ].…”
Section: Biological Mechanisms For In Situ Pulmonary Immunothrombosismentioning
confidence: 99%
See 1 more Smart Citation